S109 Targeting the prostacyclin pathway in the treatment of connective tissue disease associated pulmonary arterial hypertension (pah): insights from the randomised controlled griphon trial with selexipag. (15th November 2016) - Coghlan, G; Gaine, S; Channick, R; Scala, L Di; Galiè, N; Ghofrani, HA; Hoeper, MM; Lang, I; McLaughlin, V; Preiss, R; Rubin, LJ; Simonneau, G; et al.
Abstract : Rationale: Despite available therapies, patients with connective tissue disease-associated PAH (PAH-CTD) have a poor prognosis. The global phase III GRIPHON study (NCT01106014 ) enrolled 1, 156 patients including 334 with PAH-CTD. Compared with placebo, selexipag reduced the risk of the primary composite outcome of morbidity/mortality up to end of treatment by 41% (hazard ratio [HR] 0.59; 99% CI: 0.37–0.96) among patients with PAH-CTD. We examined the effect of selexipag vs placebo in the PAH-CTD subgroups: PAH associated with systemic sclerosis (PAH-SSc), systemic lupus erythematous (PAH-SLE) and mixed CTD (PAH-MCTD). Methods: Patients (18–75 years) were randomised 1:1 to placebo or selexipag. HRs (95% CI) were calculated using Cox regression models to determine the effect of selexipag vs placebo on morbidity/mortality. Results: Of the 334 patients enrolled with PAH-CTD, 170 had PAH-SSc, 82 PAH-SLE, and 47 PAH-MCTD; CTD sub-classification was not reported in 35 patients. Across the subgroups, the majority of patients were female (84–99%) and were receiving an endothelin receptor antagonist, a phosphodiesterase type-5 inhibitor or both at baseline (73–83%). In the PAH-SSc, PAH-SLE and PAH-MCTD subgroups, the mean (SD) age was 60.0 (10.6), 39.0 (11.3) and 48.0 (14.7) years, respectively, and 65%, 33%, and 45% were in WHO functional class III, respectively. Selexipag reduced the risk of morbidity/mortality events by 44% (HR 0.56; 95% CI: 0.34–0.91) in PAH-SSc, 34% (HR 0.66; 95% CI: 0.30–1.48) in PAH-SLE, and 53% (HR 0.47; 95% CI: 0.15–1.48) in PAH-MCTD (Figure ). The treatment effect was consistent across the subgroups (interaction test indicated no heterogeneity; p = 0.6737). By the end of study, 22 PAH-SSc, 7 PAH-SLE and 3 PAH-MCTD patients in the placebo, and 17 PAH-SSc, 4 PAH-SLE, 8 PAH-MCTD patients in the selexipag group had died. Common prostacyclin-associated side effects observed with selexipag in PAH-CTD patients generally occurred at a similar incidence to PAH-non-CTD patients and within the PAH-CTD subgroups. Conclusion: GRIPHON included the largest randomised cohort of patients with PAH-CTD to date. The treatment effect of selexipag on time to first morbidity/mortality event was consistent across the subgroups, suggesting that selexipag is an effective therapeutic option in these difficult-to-treat patients. Please refer to page A270 for declarations of interest in relation to abstract S109.